Young adult literature, libraries, and conservative activism - Gaffney, Loretta M., 1970- (Beta Phi Mu scholars., 2017)
This incisive study analyzes young adult (YA) literature as a cultural phenomenon, explaining why this explosion of books written for and marketed to teen readers has important consequences for how we understand reading in America. As visible and volatile shorthand for competing views of teen reading, YA literature has become a lightning rod for a variety of aesthetic, pedagogical, and popular literature controversies. Noted scholar Loretta Gaffney not only examines how YA literature is defended and critiqued within the context of rapid cultural and technological changes, but also highlights how struggles about teen reading matter to?and matter in?the future of librarianship and education. The work bridges divides between literary criticism, professional practices, canon building, literature appreciation, genre classifications and recommendations, standard histories, and commentary. It will be useful in YA literature course settings in Library and Information Science, Education, and English departments. It will also be of interest to those who study right wing culture and movements in media studies, cultural studies, American studies, sociology, political science, and history. It is of additional interest to those who study print culture, publishing and the book, histories of teenagers, and research on teen reading. Finally, it will offer those interested in teenagers, literature, libraries, technology, and politics a fresh way to look at book challenges and controversies over YA literature.